Financing Management for Poor Students: Internal or External? - Iqmatul Pratiwi (Lectura : Jurnal Pendidikan, 2023)
There are many children who do not go to school, they are more concerned with making a living for their survival. Even though the government has provided assistance to elementary schools in the form of Assistance for Poor Students, Jakarta Smart Card, and Smart Indonesia Program. The aim of this article is to describe whether the problem of financing education comes from internal or external because the government has provided inexpensive and free education in accordance with Article 31 of the 1945 Constitution. This research used a qualitative approach with case study design. This research used interview and observation techniques with stakeholders at public elementary schools in the Tebet area. Then conducted interviews with the principal, vice principal, treasurer, committee, class coordinator, and parents. Both internal and external factors are mutually sustainable, if one of the two does not support it will have an impact on children’s education. This research is more directed to internal factors, namely family factors, where financial management in the family is regulated by the parents. On average, they set aside 20% of their income for their children’s education. Sometimes some parents borrow money from relatives and neighbors if the situation is urgent.